2011
DOI: 10.1016/j.neuroimage.2010.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring in language perception: Electrophysiological and hemodynamic responses to spelling violations

Abstract: The monitoring theory of language perception proposes that competing representations that are caused by strong expectancy violations can trigger a conflict which elicits reprocessing of the input to check for possible processing errors. This monitoring process is thought to be reflected by the P600 component in the EEG. The present study further investigated this monitoring process by comparing syntactic and spelling violations in an EEG and an fMRI experiment. To assess the effect of conflict strength, misspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 67 publications
6
38
0
Order By: Relevance
“…However, the results of a difference wave analysis confirmed that the amplitude of the P600 effect elicited by letter transpositions did not differ across these two word types. Our findings replicate previous studies that have also found an LPC/P600 effect to misspelled words in a sentence context (e.g., Van de Meerendonk, et al, 2011; Vissers, et al, 2006). This component is known to be elicited in circumstances in which there is some sort of “reanalysis” or “repair” process that must take place—either due to the presence of overt grammatical errors (Hagoort, Brown, & Groothusen, 1993), garden path sentences (Osterhout & Holcomb, 1992), difficult but grammatical wh-constructions (Gouvea, Phillips, Kazanina, & Poeppel, 2010), or even from musical sequence violations (Patel, Gibson, Ratner, Besson, & Holcomb, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the results of a difference wave analysis confirmed that the amplitude of the P600 effect elicited by letter transpositions did not differ across these two word types. Our findings replicate previous studies that have also found an LPC/P600 effect to misspelled words in a sentence context (e.g., Van de Meerendonk, et al, 2011; Vissers, et al, 2006). This component is known to be elicited in circumstances in which there is some sort of “reanalysis” or “repair” process that must take place—either due to the presence of overt grammatical errors (Hagoort, Brown, & Groothusen, 1993), garden path sentences (Osterhout & Holcomb, 1992), difficult but grammatical wh-constructions (Gouvea, Phillips, Kazanina, & Poeppel, 2010), or even from musical sequence violations (Patel, Gibson, Ratner, Besson, & Holcomb, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…In general, misspelled words in sentences elicit a late posterior positivity, or P600 component, beginning roughly 500 ms after target onset, with a scalp distribution largely focused over posterior electrode sites. This effect has been elicited by letter addition misspellings (i.e., broome for broom ; Münte, Heinze, Matzke, Wieringa, & Johannes, 1998) and pseudohomophones of target words (i.e., bouks for books ; Van de Meerendonk, Indefrey, Chwilla, & Kolk, 2011; Vissers, Chwilla, and Kolk, & 2006). Furthermore, the size of the P600 elicited by the misspelling has been found to be bigger for expected than unexpected words, and absent for anomalous words.…”
Section: Methodsmentioning
confidence: 99%
“…It has proven difficult to localize the neural generators underlying the P600 (Friederici, 2011). For one thing, consistent with the above hypothesis, a number of studies using fMRI have linked the P600 to the lIFG (see van de Meerendonk, Indefrey, Chwilla, & Kolk, 2011, for a discussion). However, attempts at reconstructing its generators using source localization have also identified the middle temporal gyrus and the posterior part of the temporal lobe as generator sites for the P600 (Kwon et al., 2005; Service, Helenius, Maury, & Salmelin, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…In parallel to these language-specific operations, an amodal conflictmonitoring system operates, whose function is to prevent behavioral mistakes by monitoring the presence of conflicting cues (for a discussion of this topic see van de Meerendonk et al, 2009van de Meerendonk et al, , 2010van de Meerendonk et al, , 2011. Previous findings point to the anterior cingulate cortex (Carter and van Veen, 2007;Taylor et al, 2007;van de Meerendonk et al, 2009) as the core area of this bilateral fronto-parietal network (e.g., Kuperberg et al, 2003Kuperberg et al, , 2008Nieuwland et al, 2012;Quiñones et al, 2014).…”
Section: The Current Studymentioning
confidence: 99%